At Home in the Empire: Reading Colonial Home Movies—The Hyde Collection (1928–1937). (January 2014) - Hariharan, Veena
How do available critical frameworks for the study of home movies and amateur film travel to the colonies? This article explores alternative paradigms by which to study the colonial archive, taking as a case study the colonial home movies and amateur films of Colonel Edgar S. Hyde, who served in British India between 1928 and 1947 and was Administrator of the Bastar State (inhabited by a large population of aboriginal Gond Tribes) between 1934 and 1940. The article begins by re-examining the politics of the home movie, and the colonial archive in particular, in terms of the "failed promise" of amateur cinema, despite its potential as a space of opposition and resistance. The author's analysis of the Hyde films, and the heterogeneous visual modes that coexist promiscuously in the footage, traces the primarily ethnographic mode of the films to the figure of Hyde as an "anthropologically-minded administrator" and to the network of influences on his work and life. The article argues that the films' ethnographic realism framed by the gaze of Hyde's amateur camera conceals rather than reveals the visual hierarchies of empire.